2012
DOI: 10.1111/aab.12000
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the control failure likelihood of the tomato leaf miner, Tuta absoluta

Abstract: Insecticide resistance is frequently associated with field control failure, but such an assessment of its likelihood seldom occurs. This phenomenon is a potential cause of the control failure of the tomato leaf miner Tuta absoluta (Lepidoptera: Gelechiidae); therefore we surveyed insecticide resistance as the control failure likelihood for a duration of 7 years in 20 field populations of this species. The insecticide label rate was used as the discriminating concentration, and the minimum efficacy threshold re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 25 publications
2
76
0
3
Order By: Relevance
“…The insect pest has been reported being on a downward incursion from north Africa towards the south, and this may have been promoted by its high reproductive capacity [46], wide host range [31], wide developmental thermal windows [29,30], continuous vegetable production across political borders, absence of effective surveillance and monitoring systems, lack of effective sanitary and phytosanitary measures and increase in intra-continental trade [47]. Moreover, resistance to conventional and new chemicals [48,49] has been reported as a contributing factor towards its invasion success [15,50]. In addition, African ecological and climatic conditions are similar to those of South American countries [16], suggesting that T. absoluta may establish and invade other countries in the southern African region.…”
Section: Discussionmentioning
confidence: 99%
“…The insect pest has been reported being on a downward incursion from north Africa towards the south, and this may have been promoted by its high reproductive capacity [46], wide host range [31], wide developmental thermal windows [29,30], continuous vegetable production across political borders, absence of effective surveillance and monitoring systems, lack of effective sanitary and phytosanitary measures and increase in intra-continental trade [47]. Moreover, resistance to conventional and new chemicals [48,49] has been reported as a contributing factor towards its invasion success [15,50]. In addition, African ecological and climatic conditions are similar to those of South American countries [16], suggesting that T. absoluta may establish and invade other countries in the southern African region.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a strong relationship between collection distance and resistance patterns [44,10,45,12]. All of these studies showed significant association of resistance with distance, and nearby populations tended to show more similar responses, as is the case for P. xylostella (L.) (Lepidoptera: Plutellidae).…”
Section: Insecticides Resistancementioning
confidence: 94%
“…Lepidopteran species such as Alabama argillacea (Lepidoptera: Noctuidae) [10], Plutella xylostella (Lepidoptera: Plutellidae) [11], and Tuta absoluta (Lepidoptera: Gelechiidae) [12] have shown resistance to several groups of insecticides. These authors studied insect populations from different locations, using different groups of insecticides with varying mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…The pest had accessed to Ethiopia in 2012 most probably from Sudan or Yemen (Goftishu et al, 2014) and Kenya in 2013 , Tanzania and Senegal in 2014 (Biondi et al, 2015;Tonnang et al, 2015), Uganda in 2015 (Tumuhaise et al, 2016), South Africa in 2016 (Visser et al, 2017). The main spread vehicle for this invasive insect species was natural dispersal means, such as wind (Gontijo et al, 2013;Sridhar et al, 2014) and human fruit and vegetable translocation processes in local and abroad markets (Karadjova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%